Homozygosity for a new mutation (Ile119-->Met) in the insulin receptor gene in five sibs with familial insulin resistance. Issue 9 (September 1994) - Hone, J; Accili, D; al-Gazali, L I; Lestringant, G; Orban, T; Taylor, S I
Abstract : Mutations in the insulin receptor gene can cause genetic syndromes such as leprechaunism that are associated with extreme insulin resistance. We have investigated a patient with leprechaunism born of a consanguineous marriage. All 22 exons of the insulin receptor gene were screened for mutations using denaturing gradient gel electrophoresis. Thereafter, the nucleotide sequences of selected exons were determined directly. The patient was homozygous for a point mutation in exon 2 of the insulin receptor gene which results in the substitution of methionine for isoleucine at codon 119. Thus, the mutant allele encodes a receptor that has a mutation in the putative insulin binding domain. Accordingly, the mutant receptor would be predicted not to transduce the insulin signal effectively. In spite of a homozygous abnormality of the insulin receptor gene and many of the clinical features of severe insulin resistance, the proband's clinical syndrome was noticeably different from previously described patients with leprechaunism who usually die within the first six months of life. There are a total of nine children in the family, five of whom are homozygous for the Ile119-->Met mutation in the insulin receptor gene, and are clinically affected with varying degrees of severity. Four unaffected sibs are clinically normal; two are heterozygous carriers of the mutant allele, one is homozygous for the normal allele, and one unaffected sib was not available for molecular studies.